Ten years of panchayati raj in Kerala: The case for a strong service delivery model - John, Moolakkattu Stephen; Chathukulam, Jos (2006)
Decentralisation requires a high trust approach of ex post review of performances rather than low trust ex ante controls. It requires Central guidance that emphasizes the principle of co-responsibility rather than hierarchy, which uses strong-arm tactics in a pro-active and nurturing way. The challenge of building effective monitoring and accountability systems from above as well as from below without undermining the legitimacy of the elected representatives is crucial for the success of decentralisation. The article makes a review of the experience of Panchayat Raj in Kerala during the last ten years and concludes that Kerala panchayat raj system is a strong case for service delivery model. The village Panchayats have become sites of local welfare and effective service delivery and many poor people now frequent the Panchayat office for pensions and other benefits. - Reproduced.
Keywords: Panchayat